Structures lexico-syntaxiques fondées sur le verbe viser dans l’écrit scientifique. Analyse contrastive franco-polonaise - Gabrysiak, Katarzyna (Neophilologica, 2021)
The paper offers an analysis of lexical-syntactic structures based on the verb form viser typical of a scientific text, that is a text that follows quite a stable and rigid structure. A corpus-based analysis, achieved through the use of the Scientext corpora, runs across two dimensions. The first dimension is constituted by the subject matter of the text while the other dimension concerns the relation between the author of the text and the recipient. The analysis presented is a two-stage process. At the first stage, lexical-syntactic structures are singled out. The second stage is to assign those structures to the particular parts of the text, such as Introduction, Main body, Conclusion.